DESAIN DAN PEMBUATAN NERACA ELEKTRONIK MENGGUNAKAN SENSOR KOIL DATAR BERBASIS MIKROKONTROLER AT 89C51 - , Wahyudi
The realization of electronic balance device at a low cost level with flat coil sensor has been made possible by using a microcontroller AT 89051 and a sensor specific signal processing. The principle work of physical a flat coil sensor is based on the changing inductivity of a flat coil due disturbance of conductive material in its electromagnetic field, so that eddy current on the conductive material is occurred. Changes of displacement beside a flat coil sensor with material conductive will influential on inductivity L of sensor system , that was measured as frequencies resonants. The measuring system are a flat coil sensor, analog signal, digital and displays. Result of calibrations point out that out signal from sensor system is liner relative with weight, and has relative error maximum +/- 1.77%.